Adsorption removal of antiviral drug oseltamivir and its metabolite oseltamivir carboxylate by carbon nanotubes: Effects of carbon nanotube properties and media. (1st October 2015) - Wang, Wen-Long; Wu, Qian-Yuan; Wang, Zheng-Ming; Niu, Li-Xia; Wang, Chao; Sun, Ming-Chao; Hu, Hong-Ying
Abstract: This investigation evaluated the adsorption behavior of the antiviral drugs of oseltamivir (OE) and its metabolites (i.e., oseltamivir carboxylate (OC)) on three types of carbon nanotubes (CNTs) including single-walled CNT (SWCNT), multi-walled CNT (MWCNT), and carboxylated SWCNT (SWCNT–COOH). CNTs can efficiently remove more than 90% of the OE and OC from aqueous solution when the initial concentration was lower than 10 −4 mmol/L. The Polanyi–Manes model depicted the adsorption isotherms of OE and OC on CNTs better than the Langmuir and Freundlich models. The properties of OE/OC and the characteristics of CNTs, particularly the oxygen functional groups (e.g., SWCNT–COOH) played important roles during the adsorption processes. OE showed a higher adsorption affinity than OC. By comparing the different adsorbates adsorption on each CNT and each adsorbate adsorption on different CNTs, the adsorption mechanisms of hydrophobic interaction, electrostatic interaction, van der Waals force, and H-bonding were proposed as the contributing factors for OE and OC adsorption on CNTs. Particularly, for verifying the contribution of electrostatic interaction, the changes of adsorption partition efficiency ( K d ) of OE and OC on CNTs were evaluated by varying pH from 2 to 11 and the importance of isoelectric point (pHIEP ) of CNTs on OE and OC adsorption was addressed. Graphical abstract: Highlights: First investigation on adsorption of antivirus drugs OE and OC. Three types of CNTs can efficiently adsorb OE and OC at environmental concentration. PMM can depict the adsorption isotherms of OE and OC on CNTs better than LM and FM. The properties of OE/OC and CNTs affect the adsorption processes significantly. Solution pH can affect the adsorption of OE and OC in different ways.